Effectiveness of Self-Monitoring Blood Pressure in Primary Care - Wichai Aekplakorn; Paibul Suriyawongpaisal; Rassamee Tansirisithikul; Thida Sakulpipat; Phikul Charoensuk (SAGE Publishing, 2016)
Objective: To examine the effectiveness of self-monitoring blood pressure (SMBP) in a randomized controlled trial with 12 months of follow-up in a community hospital. Methods: A total of 224 eligible patients with hypertension were randomly allocated to the SMBP (n = 111) and usual care groups (n = 113). Each patient in the SMBP group was provided with a blood pressure (BP) monitor for home BP measurement. Mixed model regression was used to compare changes in BP at months 6 and 12 and compare between groups. Results: At month 12, compared with usual care, the SMBP group had average systolic BP decreased by 2.5 mm Hg. The benefit of the SMBP was found in those aged ≥60 years, which significantly decreased by −8.9 mm Hg (95%CI = −15.1 to −2.7) compared with those in the usual care. For individuals aged 60 years and older in the SMBP group, the proportion of those with uncontrolled BP decreased from 90.9% at baseline to 38.2% at month 12 ( P < .05). However, among those aged <60 years, SMBP did not perform better than the usual care group. Conclusion: For primary care setting in urban area, the SMBP resulted in lower BP in the older persons with hypertension at 12 months. Further study on effectiveness of SMBP in other settings may be warranted.